Design, fabrication, and performance evaluation of a novel orientation independent and wickless heat spreader. (June 2020) - Kumar, Nirbhay; Sinha, Kumar Nishant Ranjan; Raza, Md. Qaisar; Verma, Ashwani; Seth, Debabrata; Jasvanth, V.S.; Raj, Rishi
Highlights: A novel wickless heat spreader is designed, fabricated, and tested. Aqueous ionic liquid solution is used as the test fluid with a 100% filling ratio. An orientation independent heat spreading mechanism is demonstrated. Bubble visualization and thermal imaging results confirm heat spreading. Near-isothermal performance from 0.5-1.0 MW/m 2 in the two-phase regime. Abstract: Concentrated heat loads from electronic components present significant thermal management challenges in defense, space, and commercial applications. Liquid-vapor phase-change promises efficient heat dissipation due to the high latent heat of vaporization of the working fluid. Here we report a novel wickless two-phase heat spreader wherein an aqueous solution of surface-active ionic liquid (SAIL) is completely filled within a narrow gap. Unlike typical two-phase passive devices in literature, our device does not rely on gravity or wicks for fluid recirculation. The force of repulsion due to the interaction of SAILs adsorbed at the liquid-vapor interfaces of thin-liquid films contained between neighboring bubbles nucleating at the hotspots is strong enough to cause bubble departure at all orientations. High-speed bubble visualization and infrared thermography suggest that these non-coalescing bubbles quickly spread over a larger area and condense to release the heat to a sink placed at a gap of 2.5 mm. This passive mechanism of heat dissipation demonstrates orientation independent and near-isothermal performance from 0.5 − 1.1 MW/m 2 in the two-phase regime. We believe that the orientation independent performance of this easy to fabricate passive device provides a platform to design next generation thermal management strategies for earth and microgravity applications.